If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 6) = 46 Reorder the terms: 2(6 + x) = 46 (6 * 2 + x * 2) = 46 (12 + 2x) = 46 Solving 12 + 2x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2x = 46 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 46 + -12 2x = 46 + -12 Combine like terms: 46 + -12 = 34 2x = 34 Divide each side by '2'. x = 17 Simplifying x = 17
| 15b^2-14b+3=0 | | x(2-x)=-3 | | -1.8=0.6x | | Graphx-9y=72 | | 8y^2+14y+3=0 | | 3(8+5v)=8v-32 | | (X-32)=50 | | 3(r+2)-5(r-8)=4+6+7r | | 2w^2-3w-9=0 | | 8x-14=3x+16 | | 2w^2-w-6=0 | | 11(4-3-2t)= | | -.7x^2+7.6x=1.5x+5.4 | | z+10=z+10 | | 27=5x-3 | | 3y^2=-y+4 | | 0.2y+1.4y-0.3y+1.4=8 | | 5(x+3)=x+3(x-5) | | 3x+4-2x=-4x+32 | | a+8(a-2)=-3-40 | | 16x^3+32x^2-1=0 | | 41+(x+2)=150 | | 2x^4-x^3-25x-12.5=0 | | 20=-.6666666x | | 1+18.1=23.9 | | 41+(41+2)=150 | | 2x-5-12=-5 | | 10-7x=-74 | | 2(x-5)-6=5x-3(5+x) | | 8(4-3x)=17x+15-8.7x | | 4x^2+8xy+y^2+3=0 | | 5(x-4)=16-x |